A STUDY ON THE OVERVIEW OF NATIONAL PAYMENTS CORPORATION OF INDIA WITH SPECIFIC REFERENCE TO PRODUCTS AND SERVICES - Kesavan, Varun (IJRDO - Journal of Business Management, 2016)
As we know that over the years India’s has witnessed a significant and drastic change in the payment and settlement system, by transforming the physical cash based economy to digital cash based economy payments and settlement system. Moreover the role of NPCI in transforming the physical cash based Indian economy to digital cash based economy payments and settlement system has been seen as a remarkable and milestone achievement in the area payments and settlement system. In this context it is significant to study the overall picture and various products and services which are being rendered by National Payments Corporation of India.